Atroposelective Phosphoric Acid Catalyzed Three‐Component Cascade Reaction: Enantioselective Synthesis of Axially Chiral N‐Arylindoles. Issue 44 (20th September 2019) - Wang, Lei; Zhong, Jialing; Lin, Xufeng
Abstract: An efficient organocatalytic atroposelective three‐component cascade reaction of 2, 3‐diketoesters, aromatic amines, and 1, 3‐cyclohexanediones has been developed for the highly enantioselective synthesis of axially chiral N‐arylindoles. The success of this method derives from the use of a newly developed second‐generation chiral spirocyclic phosphoric acid as the catalyst. In addition, this protocol was extended to the synthesis of an axially chiral monophosphorus ligand. Abstract : About the axis : The first organocatalytic atroposelective three‐component cascade heteroannulation of 2, 3‐diketoesters, aromatic amines, and 1, 3‐cyclohexanediones has been developed. A wide range of axially chiral N‐arylindoles were obtained in high yields and ee  values by using a spirocyclic phosphoric acid catalyst. DCM=dichloromethane.